Penerapan Manajemen Bisnis dan Konsep Kewirausahaan dalam Pendidikan di SMP Swasta Pahlawan Nasional - Ardila, Ovi; Hakim, Maulana; Hasibuan , Ira Damayanti; Malaya , Luthfi; Aprilia , Gusti; Zauabi , Madar (Yayasan Amanah Nur Aman, 2025)
This research is motivated by seeing how important the implementation of business management is applied in the world of education. One of them is by implementing entrepreneurs . Regulation of the Minister of National Education Number 13 of 2007 concerning Principal Standards, one of which is entrepreneurial competency. This competency is the latest competency that must be possessed by the principal, in order to realize the independence of educational institutions. To be able to apply this competency is not easy. SMP Swasta Pahlawan Nasional is an independent institution because it has implemented business units. For this reason, the author conducted this research, namely to find out and answer